2017
DOI: 10.1111/jcpp.12765
|View full text |Cite
|
Sign up to set email alerts
|

Cannabis use and psychotic‐like experiences trajectories during early adolescence: the coevolution and potential mediators

Abstract: Background:The authors sought to model the different trajectories of psychotic-like experiences (PLE) during adolescence and to examine whether the longitudinal relationship between cannabis use and PLE is mediated by changes in cognitive development and/or change in anxiety or depression symptoms. Methods: A total of 2,566 youths were assessed every year for 4-years (from 13-to 16-years of age) on clinical, substance use and cognitive development outcomes. Latent class growth models identified three trajector… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
1
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(37 citation statements)
references
References 51 publications
(81 reference statements)
1
32
1
3
Order By: Relevance
“…(, ) twice showed that a subset of young adolescents reporting moderate psychotic‐like experiences showed a particular sensitivity to the effects of cannabis use on escalation of psychotic‐like experiences. These findings have been replicated in two subsequent studies (Bourque et al., ; Wigman et al., ). These and other similar cohort studies have also identified childhood negative life events (e.g.…”
Section: Psychosis Risk and Substance Use Risk In Adolescencementioning
confidence: 61%
“…(, ) twice showed that a subset of young adolescents reporting moderate psychotic‐like experiences showed a particular sensitivity to the effects of cannabis use on escalation of psychotic‐like experiences. These findings have been replicated in two subsequent studies (Bourque et al., ; Wigman et al., ). These and other similar cohort studies have also identified childhood negative life events (e.g.…”
Section: Psychosis Risk and Substance Use Risk In Adolescencementioning
confidence: 61%
“…‘Psychotic‐like experiences’ (PLE) were recognized among the general population, but also as risk factors, predictors, or early symptoms for psychosis . They were often less severe than symptoms of psychotic disorders and transient . They were sometimes described as present in both groups with or without psychotic disorders .…”
Section: Resultsmentioning
confidence: 99%
“…4 Other definitions include 'delusions and perceptual abnormalities that exist along a phenotypic continuum with psychotic disorders lying on the extreme end' 20 and 'subthreshold expressions of the extended psychosis phenotype'. 38 symptoms of psychotic disorders 44,53 and transient. 7,48,54 They were sometimes described as present in both groups with or without psychotic disorders.…”
Section: Psychotic Experiences Distress and The Psychosis Continuummentioning
confidence: 99%
See 1 more Smart Citation
“…Concretamente, el uso de cannabis aumentaba el riesgo de psicopatología comórbida y esta, a su vez, la frecuencia de experiencias psicóticas. Estudios previos realizados en jóvenes de la población general llegan a conclusiones similares (Bourque, Afzali, O'Leary-Barrett y Conrod, 2017). Por ejemplo, Bourque et al, (2017), en un estudio longitudinal con adolescentes, encontraron que los síntomas de depresión mediaron parcialmente el vínculo longitudinal entre el consumo de cannabis y las experiencias psicóticas.…”
Section: Experiencias Psicóticas Y Cannabis: Papel Mediador De Las DIunclassified